1995
DOI: 10.1111/j.1365-2249.1995.tb03841.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycling in HIV infection: analysis ofin vivoactivated lymphocytes

Abstract: SUMMARY Infection with HIV results in increased circulating levels of T lymphocytes expressing phenotypic markers of immune activation. In the present study, using three‐colour immunofluorescence, we examined the cell cycle status of these activated cells. Activated (HLA‐DR+ CD25+ and CD38+) CD4+ and CD8+ T lymphocytes in peripheral blood were analysed for DNA content in 15 HIV + patients and 10 healthy age‐ and sex‐matched control subjects. As expected, all HIV+ patients had elevated percentage levels of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although activated cells might be more likely to undergo proliferation, it has been reported that CD8 + HLA‐DR + T cells are at an arrested phase of cell cycle and unable to divide . In order to determine the cell cycle position of CD8 + HLA‐DR − naive, CD8 + HLA‐DR − memory, and CD8 + HLA‐DR + cells and test the accuracy of those statements, simultaneous staining with 7‐amino‐actinomycin D (7‐AAD) (DNA) and pyronin Y (RNA) was performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although activated cells might be more likely to undergo proliferation, it has been reported that CD8 + HLA‐DR + T cells are at an arrested phase of cell cycle and unable to divide . In order to determine the cell cycle position of CD8 + HLA‐DR − naive, CD8 + HLA‐DR − memory, and CD8 + HLA‐DR + cells and test the accuracy of those statements, simultaneous staining with 7‐amino‐actinomycin D (7‐AAD) (DNA) and pyronin Y (RNA) was performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CD8 + T cells from HIV‐1 infected individuals are at an arrested phase of cell cycle and unable to divide . Increased expression of G1 cyclin‐dependent kinase inhibitors: p16, p21, or p27 are responsible for cell cycle arrest at G1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White blood cells (WBCs) have received little attention, despite their key role in the immune system [11,12] and that defects of WBCs are associated with a number of severe diseases [13]. Characterization of the physical properties of WBCs is therefore important not only to understand the flow and transport phenomena within blood vessels, but also potentially in the diagnosis of WBC-associated diseases and developing the technologies for single cell analysis.…”
Section: Introductionmentioning
confidence: 99%